Research on international standards on auditing : literature synthesis and opportunities for future research - Haapamäki, Elina; Sihvonen, Jukka (Elsevier, 2019)
Research on International Standards on Auditing (ISAs) would greatly benefit from a research framework that categorizes the research streams related to ISAs and suggests areas for future research. This paper reviews the current research related to ISAs and develops a framework for analysis going forward. We identify seven main research streams: the development and history of ISAs; adoption of ISAs; association between national auditing standards and ISAs; financial reporting quality; audit reports; audit efficiency; and International Financial Reporting Standards (IFRS) compliance. For each research stream, the main results are summarized. At the conclusion of our literature reviews for each research stream, we suggest areas requiring further examination.
Keywords: auditing; harmonization; International Standards on Auditing (ISA); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|